Grammatical Criticism in the Explanation of the Commentary of Ibn al-Nazim's Explanation With Mr. Ameli (Journal of the College of Basic Education, 2020)
The book of Mr. Al-Amali (Explanation Shawahd explain the son of Nazem) a series of episodes followed in the annotations of grammatical evidence throughout the ages and is a book worthy of study and analysis of the rich in the views and a variety of guidance and to carry the material rich in all levels of language and (Muhammad Ali Hobei al-Raba'i), which he achieved, and he produced a commendable output for him, a factor in which a comprehensive linguistic study, speaking of IbnNazem, his biography, and grammatical evidence in which there is some detail.The research is organized on two topics: the words of acceptance, which are (appearance, argument, necessity, rare, and so, and agreed, support them). And the words of rejection. (First, void, distant, the illusion of falling, abnormal, weakness, wrong, not something, not free of something, what is not good for him, the trash, and they, and what is in it, responds). It is necessary to point out that there is a difference in the sizes of the subjects, which is required by the scientific article on the one hand and that Mr. Al-Amli neglected to talk about the linguistic evidence in many of the issues and talk in the matters of rogue and rhetorical, which made a difference in the size of scientific material in the mabahith Linguistic second hand. And God asks that Vid this research reader and researchers in the field of specialization.